Cost Benefit Analysis of Residential PV Systems in Aegean Region - DÜNDAR, Uğurcan; Metin, Seyfi Erol (My University, 2019)
Turkey is among the countries that have high dependency to imported energy resources, with limited indigenous resources. The current rate of import dependency of primary energy supply is above 70%. This is not only a risk on energy supply security, but also a tremendous pressure on economy. In addition increasing awareness on environmental issues, higher pressure on economy to produce self sufficient energy supply resources, Turkey has shown an increasing support for the renewable energy systems. Owing to to her great positioning with regards to certain renewables, such as sun and geothermal, Turkey has been able to implement several renewables projects and the existing capacity has reached to 5.5 GW level, as of 2018. The potential is equivalent to 2737 hours of sunshine duration with solar radiation capacities reaching to 2900 in southern parts of the country. Given this potential, the objective of this sturdy is to implement a cost- benefit analysis, on household PV systems, in 3 pilot sites , in the Aegian Region of Turkey, chosen for the purpose of this study. The cost benefit analysis is simple return on investment evaluation based on direct investment and operational costs. The feed in tariffs are not considered since they are not applicable for this case and even under these restricted small scale projects. The results show that, even under these small scale roof top solar projects there is some attractive financial benefits associated with solar projects in Turkey.
Keywords: Financial Engineering; Finansal Mühendislik